(untitled) (Czech Journal of International Relations, 2007)
Daniel H. Deudney: Bounding Power: Republican Security Theory from the Polis to the Global Village. 1st ed. Princeton: Princeton University Press, 2006, 384 stran, ISBN 0-691-11901-5 (signatura knihovny ÚMV 53 356). Robert Kagan: Dangerous Nation: America’s Place in the World from its Earliest Days to the Dawn of the Twentieth Century. 1st ed. New York: Alfred A. Knopf, 2006, 527 stran, ISBN 0-375-41105-4.